Spectroscopic investigation of the effect of microstructure and energetic offset on the nature of interfacial charge transfer states in polymer: fullerene blends - Dimitrov,SD; Azzouzi,M; Wu,J; Yao,J; Dong,Y; Tuladhar,PS; Schroeder,BC; Bittner,ER; McCulloch,I; Nelson,J; Durrant,JR (Journal of the American Chemical Society, 2019)
Despite performance improvements of organic photovoltaics, the mechanism of photoinduced electron-hole separation at organic donor-acceptor interfaces remains poorly understood. Inconclusive experimental and theoretical results have produced contradictory models for electron-hole separation in which the role of interfacial charge-transfer (CT) states is unclear, with one model identifying them as limiting separation and another as readily dissociating. Here, polymer-fullerene blends with contrasting photocurrent properties and enthalpic offsets driving separation were studied. By modifying composition, film structures were varied from consisting of molecularly mixed polymer-fullerene domains to consisting of both molecularly mixed and fullerene domains. Transient absorption spectroscopy revealed that CT state dissociation generating separated electron-hole pairs is only efficient in the high energy offset blend with fullerene domains. In all other blends (with low offset or predominantly molecularly mixed domains), nanosecond geminate electron-hole recombination is observed revealing the importance of spatially localized electron-hole pairs (bound CT states) in the electron-hole dynamics. A two-dimensional lattice exciton model was used to simulate the excited state spectrum of a model system as a function of microstructure and energy offset. The results could reproduce the main features of experimental electroluminescence spectra indicating that electron-hole pairs become less bound and more spatially separated upon increasing energy offset and fullerene domain density. Differences between electroluminescence and photoluminescence spectra could be explained by CT photoluminescence being dominated by more-bound states, reflecting geminate recombination processes, while CT electroluminescence preferentially probes less-bound CT states that escape geminate recombination. These results suggest that apparently contradictory studies on electron-hole separation can be exp